102 PROMOTING BRAIN HEALTH IN AN INTEGRATED CARE OUTREACH PROGRAMME. (18th November 2021) - Mc Carthy, C E; O'Malley, K; Mannion, E; Geoghegan, J; Costello, M; Conry, M; Flanagan, L; Corry, M; Reddin, C; Murphy, R; Waters, R; O'Donnell, M; et al.
Abstract: Background: Lifestyle modifications, in older at risk populations, may prevent or slow the rate of cognitive decline. Promotion of brain health has been recommended by the WHO and other governing bodies. Supporting patients in making these lifestyle changes, however, can be complex. Generic guidance may not apply to all in a heterogenous and frail patient cohort, when physical mobility may be limited and weight loss/nutrition a concern. We sought to review current practices and barriers to brain health guidance in a regional integrated care outreach programme (ICOP). Methods: From March–June'21 the comprehensive geriatric assessment (CGA) of consecutive patients were reviewed. Those presenting with cognitive complaints, for their first assessment, were included. Demographic data and data on screening for hearing impairment and sleep disturbance were collected, in addition to information on physical activity and nutritional risk. Whether information and guidance on aspects of brain health was given was also assessed. Results: 30 patients met the inclusion criteria. The mean age was 80.3 and the mean clinical frailty scale (CFS) was 4.4. Hearing impairment was present in 20% (n = 6), with no information available in 10% (n = 3). All patients were screened for sleep disturbance, with 13% (n = 4) not fully satisfied with their sleep. Mobility aids, assistance or supervision were required in 40% (n = 12), and 23% (n = 7) were at medium or high malnutrition risk. Only 30% (n = 9) cooked their own meals. Generic brain health advice, or advice about sleep was documented in 30 (n = 9), without hearing impairment advice documented in any patient. Conclusion: There are several barriers to brain health advice in the ICOP setting, with only 30% of patients having brain health advice documented. We are currently developing patient information leaflets on brain health, that will take potential barriers into account. Dedicated and specific information on local hearing services is also in development, as part of an ongoing quality improvement project.